2015
DOI: 10.1371/journal.pone.0117476
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity Threat Motivates Science-Discrediting Online Comments

Abstract: Experiencing social identity threat from scientific findings can lead people to cognitively devalue the respective findings. Three studies examined whether potentially threatening scientific findings motivate group members to take action against the respective findings by publicly discrediting them on the Web. Results show that strongly (vs. weakly) identified group members (i.e., people who identified as “gamers”) were particularly likely to discredit social identity threatening findings publicly (i.e., studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 58 publications
(85 reference statements)
4
71
0
1
Order By: Relevance
“…are perceived as identity-threatening and trigger ego-protective responses that motivate individuals to restore a sense of self-worth (Nyhan & Reifler, 2015b), which includes undermining and counter-arguing the refutation and reinforcing the original belief. For example, Nauroth and colleagues have shown that individuals who strongly self-identify as "gamers" (compared with weaker selfidentification) will more likely negatively criticize research reports on the negative effects of video games, discredit scientists responsible for such reports, and experience more anger (Nauroth et al, 2014(Nauroth et al, , 2015.…”
Section: Self-concept and Threat Appraisalsmentioning
confidence: 99%
See 3 more Smart Citations
“…are perceived as identity-threatening and trigger ego-protective responses that motivate individuals to restore a sense of self-worth (Nyhan & Reifler, 2015b), which includes undermining and counter-arguing the refutation and reinforcing the original belief. For example, Nauroth and colleagues have shown that individuals who strongly self-identify as "gamers" (compared with weaker selfidentification) will more likely negatively criticize research reports on the negative effects of video games, discredit scientists responsible for such reports, and experience more anger (Nauroth et al, 2014(Nauroth et al, , 2015.…”
Section: Self-concept and Threat Appraisalsmentioning
confidence: 99%
“…According to Eccles (2009), individuals engage in activities, behaviors, and tasks to validate their identities. As a result, individuals will not be motivated to engage in activities inconsistent with their self-image and personal and social identities (Eccles, 2009;Nauroth et al, 2014Nauroth et al, , 2015, such as accepting information that undermines valued or salient aspects of identity. Thus, situations perceived as aversive to attaining identity-related needs, such as the need to maintain identity integrity, ought to have negative value that can lead to experiencing negative emotions (Pekrun & Perry, 2014).…”
Section: Self-concept and Emotions In Reading And Knowledge Revisionmentioning
confidence: 99%
See 2 more Smart Citations
“…Si bien el discurso político, noticioso y editorial sobre la inmigración o el racismo ha sido más abordado (Zapata-Barrero & Van Dijk, 2007;Bañón, 2008;Serradell & Munté, 2010), el de las redes sociales y la web 2.0 son más recientes, aunque también arrojan datos sobre la influencia de esos discursos en la concepción del otro (Nauroth et al, 2015;Hsueh, Yogeeswaran & Malinen, 2015).…”
Section: Introductionunclassified